Home-Based Aerobic and Resistance Exercise Interventions in Cancer Patients and Survivors: A Systematic Review - Batalik, Ladislav; Winnige, Petr; Dosbaba, Filip; Vlazna, Daniela; Janikova, Andrea (Cancers, 2021)
Cancer is a chronic disease requiring long-term treatment. Exercise interventions are increasingly being recognized as an important part of treatment and supportive cancer care for patients and survivors. Previous reviews have evaluated the benefits of exercise interventions in populations of patients under supervision at a center, but none have explored the possibilities of a home-based (HB) approach in exercise during cancer rehabilitation and the period immediately following the end of cancer treatment. The aim of this descriptive systematic review was to identify the literature focusing on the health effects of HB exercise interventions in cancer survivors and to evaluate the methodological quality of the examined studies. Relevant studies were identified by a systematic search of PubMed and the Web of Science until January 2021. Nine randomized controlled trials were included. Most studies were on aerobic and resistance exercises, and the frequency, duration, intensity, and modality varied across the different interventions. Improvements in cardiorespiratory fitness (CRF), physical activity (PA) levels, fatigue, health-related quality of life (HRQOL), and body composition have been reported. However, all the studies were limited in methodology and the reporting of results. Nevertheless, the evidence in this new area, despite the methodological limitations of the studies, suggests that HB exercise interventions are feasible, and may provide physiological and psychological benefits for cancer survivors during the rehabilitation period. A methodologically rigorous design for future research is essential for making progress in this field of study.